2020
DOI: 10.1029/2019jd031697
|View full text |Cite
|
Sign up to set email alerts
|

Variations of Stable Isotopic Composition in Atmospheric Water Vapor and their Controlling Factors—A 6‐Year Continuous Sampling Study in Nanjing, Eastern China

Abstract: Long-term continuous monitoring of water vapor isotopes has great potential to improve our understanding of mechanisms that control stable isotope variations in hydrological processes, which is essential for accurate interpretation of isotopic proxy records. Here we presented a 6-year daily data set of stable isotopes in atmospheric water vapor (δ 18 O v , δD v , and d-excess v) and precipitation (δ 18 O p , δD p , and d-excess p) at Nanjing in Eastern China, an area under the influence of the East Asian Monso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 98 publications
(167 reference statements)
2
15
0
Order By: Relevance
“…The analytical uncertainty for 17 O‐excess is ∼5 per meg. In addition, the d‐excess measurements performed on samples from both snow pits were conducted at the School of Geography and Ocean Science, Nanjing University (NJU), China, by a wavelength cavity ring‐down spectroscopic technique (Model: Picarro L2120‐i), which has an analytical uncertainty less than 1.0‰ (Li et al., 2020; Tang et al., 2015). An earlier study has determined the chronology of the 3.0‐m‐deep snow pit based on known ages for reference layers for the Pinatubo volcanic eruption (Philippines, June 1991), identified by the non‐sea‐salt sulfate peak and the 1963 radioactive nuclear bomb horizon, as determined by the maximum β activity (Hua et al., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The analytical uncertainty for 17 O‐excess is ∼5 per meg. In addition, the d‐excess measurements performed on samples from both snow pits were conducted at the School of Geography and Ocean Science, Nanjing University (NJU), China, by a wavelength cavity ring‐down spectroscopic technique (Model: Picarro L2120‐i), which has an analytical uncertainty less than 1.0‰ (Li et al., 2020; Tang et al., 2015). An earlier study has determined the chronology of the 3.0‐m‐deep snow pit based on known ages for reference layers for the Pinatubo volcanic eruption (Philippines, June 1991), identified by the non‐sea‐salt sulfate peak and the 1963 radioactive nuclear bomb horizon, as determined by the maximum β activity (Hua et al., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…SM has negative δ 18 O w (−7.41‰) and d w (14.47‰) values, indicating that progressive rainout along long-distance transport pathways of air masses should be considered (Figures 5B, 6B). Previous studies have also found that the negative dexcess values during the summer season are associated with weak kinetic isotope fractionation over the oceanic source with warm and humid conditions, whereas the cold and dry air masses from both continental and local sources cause high d-excess values in autumn and winter (Liu et al, 2008;Li et al, 2020). Our results (Figures 3, 5, 6) are consistent with these findings and suggest Frontiers in Environmental Science frontiersin.org that moisture sources play a significant role in explaining the observed seasonal variation in δ 18 O p .…”
Section: Seasonal Variation Of Precipitation Isotopesmentioning
confidence: 90%
“…Our results (Figures 3, 5, 6) are consistent with these findings and suggest Frontiers in Environmental Science frontiersin.org that moisture sources play a significant role in explaining the observed seasonal variation in δ 18 O p . Notably, there is no single source of water vapor on a seasonal scale, with various water vapor mixing and dominating by turns occurring at different periods (Li et al, 2020;Guo et al, 2021). Therefore, due to the seasonal variation in precipitation isotopes in the region, the paleoclimate δ 18 O records of this region may be able to reflect the strength of EASM in the region.…”
Section: Seasonal Variation Of Precipitation Isotopesmentioning
confidence: 99%
“…The development of laser-based spectroscopic isotope analysis made the precise, highresolution and real-time measurements of both vapor δ 18 O and δ 2 H available in recent decades. However, most of the in-situ observation are station-based (e.g., Li et al(2020), Tian et al(2020), Steen-Larsen et al(2017)), or performed during ocean cruises (Thurnherr et al, 2020;Bonne et al, 2019;JingfengLiu et al, 2014;Kurita, 2011;Benetti et al, 2017). These observations provided new insight on moisture sources, synoptic influences, and sea surface evaporation fractionation processes.…”
Section: Introductionmentioning
confidence: 99%